ANALISIS YURIDIS TANGGUNG JAWAB NOTARIS TERHADAP AKTA YANG DIBUAT NOTARIS: STUDI KASUS PUTUSAN PENGADILAN NEGERI CIBINONG NOMOR 46/Pdt.G/2023/PN. Cbi - Seprianatha, Irsan; Fendri, Azmi; Delfiyanti, Delfiyanti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
A notary has the authority to create authentic deeds as regulated by Law No. 2 of 2014 on Notarial Positions. This authority carries significant responsibility, both civilly, criminally, and administratively, concerning the validity and conformity of the deeds created. This study analyzes the notary’s responsibility in creating authentic deeds, focusing on Case No. 46/Pdt.G/2023/PN Cbi, which involves a lawsuit against a notary for errors in creating a deed that did not reflect the parties' intentions. The research findings show that although the court decided to annul the deed and recognized the unlawful act, the judges' decision lacked comprehensiveness as it did not include specific regulations from the UUJN in their considerations. This study suggests that judges should more thoroughly consider provisions in UUJN and enhance supervision over notaries to ensure the validity of deeds created in accordance with applicable procedures.